2009
DOI: 10.1038/sj.bjc.6605489
|View full text |Cite
|
Sign up to set email alerts
|

Class III β-tubulin expression and in vitro resistance to microtubule targeting agents

Abstract: BACKGROUND: Class III b-tubulin overexpression is a marker of resistance to microtubule disruptors in vitro, in vivo and in the clinic for many cancers, including breast cancer. The aims of this study were to develop a new model of class III b-tubulin expression, avoiding the toxicity associated with chronic overexpression of class III b-tubulin, and study the efficacy of a panel of clinical and pre-clinical drugs in this model. METHODS: MCF-7 (ER þ ve) and MDA-MB-231 (ERÀve) were either transfected with pALTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(153 citation statements)
references
References 29 publications
(36 reference statements)
5
146
1
1
Order By: Relevance
“…A reduction in the amount of class III b-tubulin isotype was observed in nonsmall cell lung carcinoma cells with acquired resistance to CA-4 (Wehbe et al, 2005). These findings contradict other studies demonstrating that the therapeutic efficacy of colchicine sitebinding agents is not influenced by changes in class III b-tubulin expression (Stengel et al, 2010). However, both studies support the findings that the combretastatins are active in cells overexpressing class III b-tubulin displaying resistance to paclitaxel.…”
Section: Cell Survival/resistancecontrasting
confidence: 57%
“…A reduction in the amount of class III b-tubulin isotype was observed in nonsmall cell lung carcinoma cells with acquired resistance to CA-4 (Wehbe et al, 2005). These findings contradict other studies demonstrating that the therapeutic efficacy of colchicine sitebinding agents is not influenced by changes in class III b-tubulin expression (Stengel et al, 2010). However, both studies support the findings that the combretastatins are active in cells overexpressing class III b-tubulin displaying resistance to paclitaxel.…”
Section: Cell Survival/resistancecontrasting
confidence: 57%
“…Although many studies have focused on paclitaxel, such characteristics might also be pertinent for docetaxel. Interestingly, recent reports further showed that βIII-tubulin confers resistance to microtubule-destabilizing agents such as vinorelbine in breast cancer cells (44). In the setting of non-small cell lung cancer, βIII-tubulin was shown to affect significantly the response to both tubulin-targeting agents and DNA-damaging agents (45).…”
Section: Discussionmentioning
confidence: 99%
“…The growth inhibitory IC 50 for STX1383 and STX2171 in LNCaPwt and PC-3 prostate cancer cells plated at a density of 3500 cells/well was determined as described previously (Stengel et al 2010). A known anti-proliferative compound, STX140 (Leese et al 2006, Day et al 2009a, was included in the assay as a positive control.…”
Section: Proliferation Assaymentioning
confidence: 99%